Ways to increase the traction efficiency of modular draft device - Nadykto, Volodymyr; Надикто, Володимир Трохимович; Надыкто, Владимир Трофимович; Kiurchev, Volodymyr; Кюрчев, Володимир Миколайович; Кюрчев, Владимир Николаевич; Chaplinskyi, Andrii; Чаплінський, Андрій Петрович; Чаплинский, Андрей Петрович; Aiubov, Abdulmelik; Аюбов, Абдулмелік Мухтарович; Аюбов, Абдулмелик Мухтарович (My University, 2021)
The versatility of tractors can be increased by using them as a part of a modular draft device (MDD). MDD consists of energetic (EM) and technological (TM) modules. EM is a high-energy tractor with a 2WD or 4WD wheel arrangement and a traction force of 14-16 kN. ТМ is an additional axle with an active drive of its wheels. By connecting TM to the rear hitch linkage (RHL) of EM, the tractive effort of the entire MDD, which has a 4WD or 6WD wheel arrangement, increases to 32-36 kN. MDD can function as a road-rail vehicle. Depending on the traction resistance, MDD can be used both as part of an EM+TM or as a single EM. According to the research results, it was found that the maximum traction efficiency (TE) of MDD with a 6WD wheel arrangement is about 10% higher than that of MDD with a 4WD wheel arrangement. The TE value of MDD increases with an increase in the inclination of EM rear hitch linkage top link. The increase in MDD's tractive efficiency is facilitated by an increase in the coefficient of kinematic discrepancy in the drive of the EM and TM wheels from 1.00 to 1.05
Keywords: versatility of tractors; modular draft; high-energy tractor; rear hitch; maximum traction efficiency; increase in MDD's tractive